The root environment as influenced by mulches, on two different soil types and the resulting effect on fruit yield and sunburn of 'Cripps' Pink' apples - Nicholson, Allison Frances (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.